ANALISIS PENGARUH KONDISI PSIKIS DAN KONDISI FISIK PEGAWAI PUSKESMAS TERHADAP KUALITAS PELAYANAN PUSKESMAS JETAK GETASAN KABUPATEN SEMARANG - Afandi, Pandi (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2009)
A B S T R A C T Psychical condition and Condition of Officer Physical become the determinant in serving society, particularly again to society of patient of PUSKESMAS Jetak Getasan of Sub-Province semarang, hence prima progressively psychical condition and condition of officer physical very supporting quality of service given. Target of this research is to know the each the variable its influence to service quality and also result of its analysis in confirmation [of] result of previous research. Result of hypothesis test indicate that the psychical condition officer to quality of service obtained t-test 1,933 smaller than t-table 2,0796 or sig [of] equal to 0,067 above 0,05 so that there no influence signifikan of condition of officer to quality of service, its meaning [is] psychical in a condition like any officer do not influence its quality in giving service to patient PUSKEMAS. To test the hiapotesis variable of condition of physical to quality of service obtained t-test 4,301 bigger than t-table 2,0796 or sig [of] equal to 0,00 below/under 0,05, hence condition of officer physical have an effect on the significant to quality of its meaning service is prima progressively the condition of officer physical progressively goodness of[is quality of its service and downhill progressively the condition of fficer physical hence downhill progressively also the quality of its service. Result of test simultan obtained F-test 15,168 bigger than equal to F-Table equal to 3,467 by sig 0,00 below/under 0,05 ,so there are influence simultan which psychical signifikan condition variable and condition of officer physical to quality of service. Level of the influence contribution shown by result of coefficient diterminasi ( R-Square) 59,1 % and the rest 40,9 % influenced by other variable. Giving apresiasi and appreciation and improve the accomplishment of physical requirement be fitter and prima in giving service and also always sprier, empathy and listen carefully to represent the suggestion given by researcher from this research result, besides researcher also recommend to other researcher for the follow-up of result of research in. Keyword : Psychical Condition, Condition of physical and Quality of service